Música en el desarrollo del lenguaje verbal en niños de 3 a 4 años. - CHENCHE VERGARA GUADALUPE SELENA (2024)
Music has been used throughout history for various purposes, such as teaching support for the development of skills and abilities. During early childhood, children have problems with verbal language, so educational institutions represent a problem for their education and at the same time restrict the learning process, which harms their learning. In the research, a qualitative approach was used together with field and documentary research through books, magazines, theses, scientific articles, etc. As a technique, the interview directed to the teacher and the observation sheet for the children were applied. This research is aimed at teachers and students with the purpose of benefiting children from 3 to 4 years old in the development of verbal language. By applying music for the development of verbal language, the students will obtain a significant learning in which they can have greater fluency and improvement in communication that will be helpful in the development of their skills and abilities. In conclusion, music is crucial for the development of verbal language by allowing students to integrate effectively into the educational environment, achieving multiple benefits in their education.